The Many Daughters Of Afong Moy : a novel - Ford, Jamie, 1968- (New York : Atria Books, 2022)
"From the New York Times bestselling author of Hotel on the Corner of Bitter and Sweet comes a powerful novel about the love that binds one family of women across generations. Dorothy Moy breaks her own heart for a living. As Seattle's former poet laureate, that's how she describes channeling her dissociative episodes and mental breakdowns into her art. But when her five-year-old daughter, Annabel, exhibits the same behavior and begins remembering things and events she has never experienced, Dorothy believes the past has truly come to haunt the present. If she doesn't take radical steps, her daughter will be doomed to face the same debilitating depression that has marked her life. Through epigenetic therapy-an experimental treatment designed to mitigate inherited trauma-Dorothy intimately connects with the past generations of women in her family: Faye Moy, a nurse in Burma serving with the Flying Tigers; Afong Moy, the first Chinese woman to set foot in America; Zoe Moy, a student in England at a famous school with no rules; Lai King Moy, a girl quarantined in San Francisco during a plague epidemic; and Greta Moy, a tech executive with a unique dating app. Through reliving their painful stories, Dorothy comes to understand the true cost of inherited pain. As the past bleeds into the present, Dorothy discovers that trauma isn't the only thing she's inherited. A stranger is searching for her in each time period. A stranger who's loved her through all of her genetic memories. And that person is most certainly not her current husband, Louis. To protect her daughter's future, Dorothy must break the cycle and find a way to cross time and resolve all past traumas, to find the love that has long been waiting, and find peace for Annabel. Even if it means she must sacrifice her only chance at life and happiness"--.
new book fall 2022.
Keywords: Women; Mental illness; Psychological fiction; Mothers and daughters; Epic fiction; Psychic trauma